2009
DOI: 10.1021/nl8036799
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of InN Nanowires and the Influence of the Native Indium Oxide Formed at Their Surface

Abstract: The electrical properties of InN nanowires were investigated in four-point probe measurements. The dependence of the conductance on the wire diameter allows distinguishing between "core" bulk (quadratic) and "shell" sheet (linear) contributions. Evidence of the formation of a thin In(2)O(3) layer at the surface of the nanowires is provided by X-ray core level photoemission spectroscopy. The shell conductivity is therefore ascribed to an electron accumulation layer forming at the radial InN/In(2)O(3) interface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
71
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 21 publications
11
71
2
Order By: Relevance
“…Furthermore, also for InN nanowires the surface conductance can govern the electrical transport. 12,13 If such a surface layer were-within a certain diameter range-relevant for the overall transport properties of our InAs nanowires, one might naively expect that the resistance would be proportional to the inverse of the diameter, i.e., a weaker dependence than we find. But this reasoning only holds for constant electron density and mobility, whereas we will show below that both depend on diameter.…”
Section: Diameter-dependent Conductance Of Inas Nanowiresmentioning
confidence: 70%
“…Furthermore, also for InN nanowires the surface conductance can govern the electrical transport. 12,13 If such a surface layer were-within a certain diameter range-relevant for the overall transport properties of our InAs nanowires, one might naively expect that the resistance would be proportional to the inverse of the diameter, i.e., a weaker dependence than we find. But this reasoning only holds for constant electron density and mobility, whereas we will show below that both depend on diameter.…”
Section: Diameter-dependent Conductance Of Inas Nanowiresmentioning
confidence: 70%
“…8,[19][20][21][22][23][24][25][26][27][28][29][30] For example, in general, the currently reported nominally undoped InN is n-type degenerate, with the residual electron densities in the range of ∼ 1 × 10 18 cm −3 , or higher. 8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires. 8,11,21,22,25,36 In this regard, significant efforts have been devoted to understanding the fundamental surface charge properties of InN.…”
mentioning
confidence: 69%
“…In terms of nonpolar InN surface, recent studies suggest that the surface electron accumulation may depend critically on the surface states, impurities, stoichiometry, and polarity; 27,37 and the absence of electron accumulation at nonpolar surface has been predicted. 23,27 In experiments, however, only recent cross-sectional scanning photoelectron microscopy and spectroscopy studies at nonpolar cleaved InN surface exhibits the unpinned E F , 38,39 while in general the electron accumulation is prevalently observed at nonpolar InN surface; 22,34,35 the electron accumulation issue at nonpolar InN surface had remained elusive.…”
mentioning
confidence: 99%
“…Considering that charge transport in small diameter NW (<60 nm) occurs mainly through the single crystal core, 49 the conductivity of SFLS NWs will mainly depend on charge carrier scattering from defects as described by the Eq. 4 50 :…”
Section: Eq 2 ( ) = +mentioning
confidence: 99%